Criminal responsibility without alternative possibilities? The dilemma of freedom and the structure of ascription (De Legibus - Law Journal, 2022)
This essay is about some connections between the idea according to which free will and determinism are mutually compatible and the fundamentals of criminal imputation. It is sustained that the Principle of Alternative Possibilities remains indispensable as a starting point, without damage to its integration into a broader model, able to cover those situations where the moral agent intentionally (at least by negligence) produces (or do not avoid) the conditions of his own lack of liability in ordinary or general terms.
Keywords: criminal responsibility; free will; indeterminism; determinism; compatibilism; freedom of action; Principle of Alternative Possibilities (PAP); Source Model (SM); causing the conditions of one’s own lack of liability; extraordinary imputation